GREAT MUSICAL FORMS DEDICATED TO SAINTS CYRIL AND METHODIUS - Towarek, Piotr (Forum Teologiczne, 2023)
This article takes a closer look at the great musical forms dedicated to Saints Cyril and Methodius. These are mainly liturgical compositions related to the worship of the two saints. This group includes a medieval Mass propria (e.g. Parchment Missal no. 212 of the Cracow Chapter) and the Baroque-Classical Mass by Michael Haydn (1758). In the 19th century, the repertoire was expanded to include cantatas (Křížkovsky, Surzyński, Dinew) and hymns (Liszt, Tchaikovsky, Borodin, Pipkov), which are linked to the process of national awakening of Czechs, Slovaks, Croats and Bulgarians. The 19th and 20th centuries also saw the creation of numerous arrangements of the Ordinarium Missae in Glagolitic. These include Leoš Janáček’s monumental “Glagolská mše” (1926) and related works by Czech and Croatian composers (Říchovski, Foerster, Kožušníček, Douša, Janda, Kozinović, Novak, Sokol, Hanuš, Láník). This collection is enriched by stage works: the opera of Zhivka Klinkova (1981/2021) and oratorios and cantatas from the 20th and 21st centuries (Dinew, Širola, Krška, Andrašovan, Tučapský, Procházka, Krák). These works are based on Glagolitic liturgical tests and poetry and prose related to the upsurge of national thought in the 19th century. They show Sts Cyril and Methodius not only as preachers of the Gospel and missionaries to the Slavic peoples but also as teachers of culture, dialogue and reconciliation, and above all, as founders of the foundations of Slavic national identity. The article presented here contributes to the current theological reflection in the field of aspectual hagiology.